Fast Multipole Accelerated Boundary Integral Equation Method for Evaluating the Stress Field Associated with Dislocations in a Finite Medium (Communications in Computational Physics, 2012)
In this paper, we develop an efficient numerical method based on the boundary integral equation formulation and new version of fast multipole method to solvethe boundary value problem for the stress field associated with dislocations in a finitemedium. Numerical examples are presented to examine the influence from materialboundaries on dislocations.